2015
DOI: 10.1039/c4cy01331j
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted Article: Monodisperse CuB23nanoparticles grown on graphene as highly efficient catalysts for unactivated alkyl halide Heck coupling and levulinic acid hydrogenation

Abstract: Monodisperse CuB23 nanoparticles grown on graphene exert exceedingly high activity towards unactivated alkyl halide Heck coupling and levulinic acid hydrogenation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 141 publications
0
14
0
Order By: Relevance
“…The electron‐enriched Ru sites were beneficial for the formation of H‐species on Ru . They were also favorable for the activation of the adsorbed carbonyl (C=O) group during the hydrogenation of LA to GVL, and thus had higher catalytic activity …”
Section: Resultsmentioning
confidence: 99%
“…The electron‐enriched Ru sites were beneficial for the formation of H‐species on Ru . They were also favorable for the activation of the adsorbed carbonyl (C=O) group during the hydrogenation of LA to GVL, and thus had higher catalytic activity …”
Section: Resultsmentioning
confidence: 99%
“…1 This class of transformations includes alkyl-Mizoroki-Heck-type reactions, constituting fundamental cross-couplings of unactivated alkyl halides with alkenes. 2 In prior studies, we developed a carbonylative variant of this reaction that yields cyclic enones from alkyl iodides and pendant alkenes (Figure 1). 3 We became interested in pursuing an alternative process involving alkene difunctionalization (carboacylation).…”
mentioning
confidence: 99%
“…Bromopentacarbonylmanganese(I) and cobalt(0) carbonyl were both ineffective as catalysts (entries 2–3), as was Pd(PPh 3 ) 4 , which we have previously used in a number of catalytic C–C bond-forming reactions involving alkyl iodides (entry 4). 2e,3a,9 Amine bases could be used in the reaction, although yields were slightly diminished (entry 5). Reactions performed at various levels of CO pressure indicated that while reactions using a balloon of CO (1 atm) were unsuccessful, high pressures were not required (entries 6–7).…”
mentioning
confidence: 99%
“…As in most publications only the yield of a reaction is reported (e.g., Refs. 45,46) with no further statements on the conversion and selectivity, the reaction might be limited by maximum conversion (conversion limitation) or maximum selectivity (selectivity limitation).…”
Section: Reaction Network Flux Analysismentioning
confidence: 99%